IMPLEMENTATION OF MURABAHAH FINANCING AGREEMENT AT SHARIA RURAL BANK IN SPECIAL REGION OF YOGYAKARTA - Asyikin, Istianah Zainal; Fitriyanti, Fadia (The journal of contemporary issues in business and government, 2021)
This is a normative-empirical research aimed at determining the suitability of murabahah financing practices at Sharia Rural Bank (BPRS) in the Special Region of Yogyakarta (DIY). The results showed that the practice of murabahah financing in BPRS in DIY is carried out sequentially as follows. First, profit is determined based on the interest of conventional banks. Second, installments are calculated using the annuity formula. Third, down payment and collateral are applied to customers. Fourth, reward and punishment are applied to the customer. Fifth, financing is realized using the wakalah and murabahah agreement implemented before the murabahah object becomes the bank's property. The first to fourth practices are carried out in accordance with sharia law, excluding the fifth, which contains gharar prohibited in Shariah.